Design, synthesis, and biological activity of new endomorphin analogs with multi-site modifications. Issue 9 (1st May 2020) - Zhao, Long; Luo, Keyao; Wang, Zhaojuan; Wang, Yuan; Zhang, Xianghui; Yang, Dongxu; Ma, Mengtao; Zhou, Jingjing; Cui, Jiaming; Wang, Jing; Han, Chao-zhen-yi; Liu, Xin; et al.
Graphical abstract: Abstract: Endomorphin (EM)-1 and EM-2 are the most effective endogenous analgesics with efficient separation of analgesia from the risk of adverse effects. Poor metabolic stability and ineffective analgesia after peripheral administration were detrimental for the use of EMs as novel clinical analgesics. Therefore, here, we aimed to establish new EM analogs via introducing different bifunctional d -amino acids at position 2 of [(2-furyl)Map 4 ]EMs. The combination of [(2-furyl)Map 4 ]EMs with D-Arg 2 or D-Cit 2 yielded analogs with enhanced binding affinity to the μ -opioid receptor (MOR) and increased stability against enzymatic degradation ( t 1/2 > 300 min). However, the agonistic activities of these analogs toward MOR were slightly reduced. Similar to morphine, peripheral administration of the analog [D-Cit 2, (2-furyl)Map 4 ]EM-1 (10 ) significantly inhibited the pain behavior of mice in multiple pain models. In addition, this EM-1 analog was associated with reduced tolerance, less effect on gastrointestinal mobility, and no significant motor impairment. Compared to natural EMs, the EM analogs synthesized herein had enhanced metabolic stability, bioavailability, and analgesic properties.